Factors Associated with Tuberculosis Among Patients in HoREX Baucau, Timor-Leste, 2025 - Oqui, Maximiano; Deus, Elisa de; Mendonça Coelho, Judélia Carme; Moreira, Adriano Freitas; de Jesus Ximenes, Remígia Auxiliadora; Evaristo Obeno, Olandino; Geri de Sena Amaral, Saturnina Julieta (Rifa'Institute, 2025)
Introduction: According to the World Health Organization (2023), an estimated 10.6 million people worldwide were affected by pulmonary tuberculosis (TB) in 2022, an increase from 10.3 million in 2021 and 10.0 million in 2020. The global incidence rate in 2022 reached 133 new cases per 100,000 population. In Timor-Leste, although a slight decrease in TB incidence was reported in 2021—from 498 to 486 per 100,000 population—the burden of the disease remains high. National TB surveillance recorded 6,171 cases in 2023 and 1,570 cases in 2022, indicating ongoing transmission. Objective: This study aimed to identify the factors associated with the occurrence of tuberculosis among patients in HoREX Baucau in 2025. Methods: An analytical quantitative study with a cross-sectional design was conducted involving 89 respondents selected through purposive sampling from a population of 115 patients. Data were collected using questionnaires and checklists. Univariate analysis employed frequency distribution, bivariate analysis used the Chi-square test, and multivariable analysis applied multinomial logistic regression. Results: Nutritional status showed a significant influence on TB occurrence (p < 0.001), as did alcohol consumption (p < 0.001). Simultaneously, both factors demonstrated a significant combined effect on the incidence of tuberculosis (p < 0.001). Conclusion: Nutritional status and alcohol consumption are significant predictors of tuberculosis among patients in Hospital Referal Eduardo Ximenes (HoREX) Baucau. These findings highlight the need for strengthened nutritional support, alcohol-reduction interventions, and community-based prevention strategies